2007
DOI: 10.1007/s11434-007-0308-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photo-assisted Fenton oxidation treatment of multi-walled carbon nanotubes

Abstract: In this paper, a new and efficient way to oxidize and functionalize the multi-walled carbon nanotubes (MWNTs) has been developed by using a combination of ultraviolet (UV) irradiation and Fenton oxidation process, namely UV/Fenton oxidation treatment. Comparing with conventionally individual Fenton oxidation treatment of MWNTs, UV/Fenton combined treatment improved the etching rates and efficiencies and hence reduced the time for surface modification of MWNTs, which was proved to be an effective method in etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…These reactive oxygen species are considered the critical factor in the transformation of the FLG (Pignatello et al, 2006). These generated reactive oxygen species could attack and destroy FLG to form defect sites, and finally decompose FLG into CO 2 (Fan et al, 2007;Zhou et al, 2012). The H 2 O 2 concentration is directly proportional to the generation rate of ROS in Fenton-like reaction (Ensing et al, 2003;Neyens and Baeyens, 2003).…”
Section: Assessment Of Flg Removal At Varying Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reactive oxygen species are considered the critical factor in the transformation of the FLG (Pignatello et al, 2006). These generated reactive oxygen species could attack and destroy FLG to form defect sites, and finally decompose FLG into CO 2 (Fan et al, 2007;Zhou et al, 2012). The H 2 O 2 concentration is directly proportional to the generation rate of ROS in Fenton-like reaction (Ensing et al, 2003;Neyens and Baeyens, 2003).…”
Section: Assessment Of Flg Removal At Varying Reaction Conditionsmentioning
confidence: 99%
“…It has been developed and applied in wastewater treatment, especially in treating aromatic organic pollutants (Ensing et al, 2003;Neyens and Baeyens, 2003;Pignatello et al, 2006). Recently, the Fenton and photoFenton reactions were found to have significant implication on the treatment of carbon nanotubes (CNTs) (Allen et al, 2009;Fan et al, 2007) and GO (Bai et al, 2014;Zhou et al, 2012). Researchers have demonstrated that this simple and economical approach could effectively degrade CNTs and GO into CO 2 and some intermediate products which largely consist of adjacent aromatic rings with carboxylic acid groups (Allen et al, 2009;Bai et al, 2014;Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…除此之 外, 含有大离域π键的CNTs具有较强的光反应活性, 吸 收光后表面电子发生跃迁, 并被氧气等物质接受形成 超氧自由基等活性氧促使CNTs降解转化 [85] . •OH是CNMs转化的关键因素 [67] . 以CNTs为例…”
Section: 光降解机理unclassified
“…CNTs在紫外光照作用下首先转化为氧化中间产物, 进一步反应形成残余碎片和小分子物质. 光照诱发 CNTs降解主要有两个途径: ① CNTs在光照作用下产生电子-空穴对导致CNTs还原 [66] ; ② 光芬顿反应产生羟基自由基, 与 CNTs发生亲电加成反应 [67] (网络版彩图) [66], including the reduction of CNTs; ② Electrophilic addition between CNTs and hydroxyl radicals, which are produced by photoassisted Fenton process [67] (color online).…”
Section: 光降解机理mentioning
confidence: 99%
“…Thermogravimetric (TG) analysis [7][8][9] has been widely used for the preliminary assessment of the combustion/pyrolysis behavior of fossil fuel, biomass fuel, sewage sludge and other organic/inorganic compounds. From TG-DTG (differential thermogravimetry) curves, the initial and final mass loss temperatures, the maximum mass loss rate and its corresponding temperature can be deduced.…”
mentioning
confidence: 99%